Occurrence of Taenia species in pigs in slaughterhouses in Phu Tho province, northern Vietnam. (14th October 2020) - Nguyen, T.T.M.; Dermauw, V.; Noh, J.; Chien, N.H.; Dao, T.T.H.; Nguyen, T.G.T.; Van Hul, A.; Dorny, P.
Abstract: Pigs act as the intermediate hosts of the zoonotic tapeworms Taenia solium and Taenia asiatica, as well as of the non-zoonotic Taenia hydatigena. In Vietnam, human taeniasis and cysticercosis have been reported throughout the country; however, data on porcine cysticercosis are scarce. Our study aimed to estimate the prevalence of Taenia spp. in slaughtered pigs in two districts in Phu Tho, a mountainous province in northern Vietnam from where neurocysticercosis patients commonly originate. The carcasses of 399 pigs from 51 small-scale abattoirs were checked for cysticerci, while tongue, liver, masseter muscles, diaphragm and heart were sliced and examined. Retrieved cysticerci underwent polymerase chain reaction–restriction fragment length polymorphism and sequencing for species confirmation. Blood was also collected to detect antibodies by lentil lectin-purified glycoprotein enzyme-linked immunoelectrotransfer blot (LLGP-EITB) and recombinant T24H antigen (rT24H)-EITB and circulating antigens by B158/B60 Ag-ELISA. In two pigs, T. asiatica cysticerci were found, confirming the presence of the parasite in pigs in Vietnam at a low prevalence (0.5%; 95% exact confidence interval (CI): 0–1.19%). Cysticerci of T. solium were found in none of the pigs, although one serum sample was positive for antibodies in both LLGP-EITB and rT24H-EITB. Furthermore, a high prevalence of T. hydatigena cysticercosis was observed (18.0%; 95% Wilson score CI: 14.6–22.1%). In more than half of the T. hydatigena -positive pigs, circulating antigens were detected by Ag-ELISA, confirming that this test cannot be used to diagnose T. solium cysticercosis in this region. Finally, Spirometra erinaceieuropaei was found in one pig liver. It is the first record of this zoonotic cestode species in pigs in Vietnam. Overall, the findings confirmed the complex epidemiology of Taenia spp. in pigs in Vietnam.